PEMBUATAN GENTENG DI DESA PEJATEN DALAM FOTOGRAFI DOKUMENTER - Ni Putu Lita Nariani; Anis Raharjo; Ida Bagus Candrayana (Lp2mpp Isi Denpasar - Ps. Fotografi, 2021)
The creator was interested in bringing up the theme of Making Tiles in Pejaten Village in Documentary Photography because of the modern roof tiles from outside Bali which could be a threat from the existence of pejaten tiles. Pejaten Village has been famous for its tile making from the past until now. Pejaten tile has a characteristic that is on the tile product there is the name